OPERATIONAL AND ENERGY PERFORMANCE OF 250 kW DOUBLE WHEELED VERSUS RUBBER HALF-TRACKED TRACTORS IN THE SOYBEAN SOWING - Neto,Lauro S. (2020)
ABSTRACT The technological innovation in agriculture seeks to improve the performance of mechanized assemblies and, currently, rubber half-tracks are a valuable solution for agricultural tractors, combining traction performance and less soil compaction. The objective of the experiment was to evaluate the operational and energy performance of double wheeled versus rubber half-tracked agricultural tractors in the soybean sowing. The experiment was conducted in a strip-plot design with a double factorial arrangement (2×3). The first factor consisted of a tractor with double wheels on the front and rear axles versus a tractor with single wheels on the front axle and rubber half-tracks on the rear axle, while the second factor consisted of three different gears, with five replications, totaling 30 experimental units. The collected data were subjected to analysis of variance and, when significant, to the Tukey test. The sowing operation carried out with the half-tracked tractor was the most efficient in most of the analyzed parameters, allowing higher operational and energy efficiency in the soybean sowing.